Comparison of Two Different Method of Surgery in Ileus Meconium - Omid Amanollahi; Amin Alinejad (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
Introduction: meconium ileus occurs when the terminal ileum is obstructed by unusually tenacious meconium; it is more prevalent in neonates with cystic fibrosis. Up to 33% of neonatal small-bowel obstructions are due to meconium ileus. Symptoms such as: vomiting which may be bilious, distention of the abdomen and inability to pass meconium in the first days of life are some of the most common symptoms. Clinical presentation and x-rays are the basis of diagnosis. First step of treatment is contrast enemas under fluoroscopy and if it fails surgery should be carried out. Different surgical methods are used for operative management of uncomplicated meconium ileus. In our series, we have compared two different methods of surgery: Primary resection and anastomosis; and enterostomy using the Bishop-Koop method. We compared their effectiveness and complications. Materials and Methods: Forty neonates with ileus meconium were included in the study, 20 patients in each group. Alternating allocation that is allocating every other subject to each treatment group: for the Bishop-Koop enterostomy and anastomosis (study group) or primary resection and anastomosis (control group) was carried out .Results of treatment and complications during and after the surgery were recorded in both groups and compared together. Results: There was 3 case of mortality in the study group (%15) and 8 case of mortality in control group (%40). There was a meaningful statistical difference between mortality in the two groups (p=0/002). Conclusion: Despite the advantages of one stage repair with primary resection and anastomosis in neonates it results in a higher rate of mortality compared to the Bishop-Koop method. Thus performing the two-stage Bishop-Koop repair seems to be a more safe approach for this anomaly.